An evolutionary stable strategy for retailers selling complementary goods subject to indirect network externalities - Yi, Yuyin; Yang, Haishen (Economic modelling, 2017)
A two-population evolutionary game model is constructed for retailers and used to investigate the effect of indirect network externalities (INEs) and product complementarity on the strategic choice of marketing objective of the retailers. The results show that their strategic choice of marketing objective is correlated with market reservation price (MRP) when the strength of the INE is low. When the MRP is low, the retailers tend to adopt a strategy of profit maximization. As MRP increases, low-cost retailers adopt a strategy of revenue maximization instead of profit maximization to maximize revenue at an earlier stage than high-cost retailers. However, when the strength of the INE is high, retailers only choose a strategy of revenue maximization as their marketing objective. The probability that a retailer uses a revenue maximization strategy increases as the strength of the INE grows, and product complementarity increases, when there is an equilibrium between two pure marketing objective strategies. An optimal preference ratio for retailers may exist when the strength of INE is found to be not large enough. Numerical examples reveal that the degree of preference of retailers to maximize profit is shown to be negatively correlated with both INE and product complementarity. On the other hand, their profits are positively correlated with both of these factors. •An evolutionary game model is used to study the retailers’ choice of marking objective.•Indirect network externality (INE) has an important effect on retailers’ decision.•Revenue maximization strategy will prevail when the INE is strong enough.•The retailers’ preference towards profit maximization is negatively related to INE.•The INE and market reservation price exert quite different influences.